Eugenol isolation of Clove (Syzygium aromaticum) flower - Heru - Nurcahyo; Rizki Febriyanti; Purgiyanti Purgiyanti (Journal of Natural Sciences and Mathematics Research, 2020)
The use of alternative and complementary therapies as a treatment is growing rapidly, one of them is by alternative medicine that uses steam from essential oils / essential oils from various kinds of plants that can be inhaled and smeared to cure various conditions. Clove plants (Syzygium aromaticum) are one of the producers of essential oils that can be used as an alternative treatment for herbs. In clove oil consists of several types of components. The main component possessed by clove is eugenol which has the highest number among other components. Eugenol are important compounds in clove oil. It is a clear liquid to pale yellow compound with a refreshing and spicy aroma like dried clove flowers, giving a distinctive aroma to clove oil. The purpose of this study was to determine the eugenol content of clove flower essential oil. The use of clove flowers in this study is used to improve the competency of local products that in the future can make the outputs of competitive and economical value. This study begins with the distillation process of clove flower water to get oil up to isolation of eugenol. The identification of eugenol with TLC and testing of eugenol levels with GC-MS. The results showed that the essential oil yield was 3.16%, eugenol yield 42.92%, hRf value 11.46 and with grade 97%.©2020 JNSMR UIN Walisongo. All rights reserved.